COMPARATIVE ANALYSIS OF CYBERATTACKS ON ESTONIA, GEORGIA AND KYRGYZSTAN - Kozlowski, Andrzej (European Scientific Journal, ESJ, 2014)
The rapid informatization of the world which has started since the beginning of 90s led to the growing state interdependence from cyberspace. The Internet has become crucial to the society, economy, military of contemporary country. This situation became a new challenge for the national security and more and more often the term cyberwar has been used. Despite the fact that this phenomenon is not clearly defined the massive cyberattack on countries took place in the past. The main aim of this article is to examine three cases of these attacks: on Estonia in 2007, on Georgia in 2008 and on Kyrygysytan 2009 and to try finding similarities and differences and answer the question who carried out these strikes and why. In order to do it the following factors will be analyzed: the political background of these countries and the relation with the neighbours, the time and scale of attacks and effect of them. In conclusion the article tries to find the most difficult answer who was a perpetrator. The three hypotheses were presented with evaluation of probability of them.